(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Following previous systematical research of ortho-/meta-/para-alkoxyphenylcarbamic acid esters as antimycobacterially active compounds, the set of the derivatives containing meta-/para-alkoxyphenylcarbamoyloxy and 4-(4-fluorophenyl/2-methoxyphenyl)piperazin-1-yl moieties were tested for their in vitro activity against tuberculous strain of Mycobacterium (M.) tuberculosis CNCTC My 331/88 as well as against potential pathogenic strains of M. kansasii CNCTC My 235/80, M. avium CNCTC My 330/88 and M. kansasii 6 509/96, respectively, by applying the micromethod for the determination of the minimum inhibitory concentration (MIC). It is concludut that the molucules posscssed selatively promising activity against M. Tuberculasis and M. Kansas!!. Dhaka Univ. J. Pharm. Sci. 12(2): 103-107, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17621